Parents, adolescents, children and the human papillomavirus vaccine: a review - Walhart, T. (Int Nurs Rev, 2012)
BACKGROUND: Human papillomavirus (HPV) is a sexually transmitted infection (STI). HPV is the most common sexually transmitted infection worldwide. It is also the most common STI in adolescents. This highlights a great clinical and public health concern that must be addressed. Parents are typically involved in the clinical decision-making process of vaccine administration to children and adolescents. Therefore, understanding the acceptability of the HPV vaccination as a method to prevent STIs and certain cancers is critical. PURPOSE: To present the three primary themes that emerged from the literature: parental attitudes, parental beliefs and parental barrier towards vaccinating children and adolescents with the HPV vaccine. METHOD: A literature search using Scopus to determine parents’ attitudes and beliefs towards vaccinating children and adolescents with the HPV vaccine. The initial search included the key search terms of ‘children’ and ‘HPV vaccine’. The publication year was limited from 2006 to present. FINDINGS: The three themes greatly influence parents’ decisions to vaccinate their children.In the future, more attention needs to be paid to specific subgroups. Future research should include groups that are currently under-represented: fathers, urban populations, low socio-economic status and ethnic minorities. CONCLUSION: Since nurses worldwide are often sought as healthcare resources by parents in the clinical decision-making process, their understanding of the attitude, beliefs and barriers parents have towards the HPV vaccine is paramount.